STUDI CITRA MEREK, KUALITAS PRODUK UNTUK MENCAPAI LOYALITAS PELANGGAN PADA KONSUMEN MINUMAN KESEHATAN KALBE JAKARTA - Fellix Setyo Wisono (Universitas Mercu Buana, 2014)
Abstract. This study aims to investigate and analyze the strength and direction ofinfluence perceptions of product quality to customer loyalty, brand image of thecompany to customer loyalty, influence brand image and product qualitysimultaneously to the enterprise customer loyalty. The research data is the primarydata questionnaire of consumer health products Kalbe selected as respondents andsecondary data is the data obtained from the Annual Report Annual Kalbe.Sampling method used is purposive sampling. From a sample of 170 consumerswho shop at outlets located Kalbe health drink products in the area of Jakarta, 145consumers who shop at outlets located Kalbe health drink products in the Jakartaarea meets the criteria to be sampled. The analytical method used in this researchis multiple linear regression. The results show the brand image variables andvariable quality of the variables simultaneously affect the customer loyalty inKalbe health drink products such as coco hydro beverage products, extra jozz andlove juice. Partial variable positive effect on the brand image variable customerloyalty in Kalbe health drink products. The variable quality of the products is verypositive influence on customer loyalty variable in Kalbe health drink products.Keywords: brand image, product quality, customer loyalty.